Giochi non cooperativi a somma variabile: un'introduzione ai concetti fondamentali - Roberto Cellini; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
– The aim of this paper is to provide the reader with a simple and systematic analysis of the fundamentals of non cooperative game theory. Special attention is paid to the most controversial tools discussed throughout the specific literature concerning the problems of strategical interdipendence.
Keywords: 330